Tensile Test Analysis of Tire Tread Rubber’s Tendency to Resist Cracks - Ingyu Noh; Sangyeop Hong; Jaehoon Kim (Applied Sciences, 2022)
Among the various components of a tire, this study explores the tread portion, which has the longest contact with the ground during the summer, all-weather, and in the winter. The mechanical properties of three types of tread crack specimens were measured, and a stress–strain diagram for each specimen at low and high speeds was derived. Through the digital image correlation method, the crack tip opening displacement and angle were considered as fracture parameters and derived through equations. Subsequently, the different fracture progression regions were compared and analyzed to confirm the characteristics of the elastic displacement field. It was found that under both low- and high-speed conditions, the maximum elastic strains for the tread specimens were attained in the following order: summer, all-weather, and winter.